If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(-5x + -1v + 6) = 0 Reorder the terms: -5(6 + -1v + -5x) = 0 (6 * -5 + -1v * -5 + -5x * -5) = 0 (-30 + 5v + 25x) = 0 Solving -30 + 5v + 25x = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 5v + 30 + 25x = 0 + 30 Reorder the terms: -30 + 30 + 5v + 25x = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 5v + 25x = 0 + 30 5v + 25x = 0 + 30 Combine like terms: 0 + 30 = 30 5v + 25x = 30 Add '-25x' to each side of the equation. 5v + 25x + -25x = 30 + -25x Combine like terms: 25x + -25x = 0 5v + 0 = 30 + -25x 5v = 30 + -25x Divide each side by '5'. v = 6 + -5x Simplifying v = 6 + -5x
| y=25(3)+200 | | 4n-3=16 | | 0.27*0.56= | | y=25(3)-200 | | 4h-7g+11g-h= | | 12-3x=4+(-4x) | | x^2-11x+214=0 | | (5x+4)+(4d+5)= | | 4K-5=2k-1 | | 8x-20=64 | | http://www.thelearningodyssey.com/Assess/DPT/QIEImagesStorage/AQ13A/AQ13AI_A1322_14_stem1_1.gif | | 7a-4=4(3a+1) | | 1+(P-1)=5(P+6) | | -7x-117=12x+130 | | -9-2m-m=8m-9 | | 16x^2-40x+100=0 | | x^2-10x+16=o | | X^4+14x^2-49=0 | | -9x-15=-8x+11 | | -(3u-2x-3)= | | t/8-8=8 | | -18-3x=6-4x | | (-2+2v+2u)(-7)= | | -2*x+9=25 | | -2(r-6)=-37 | | 2*x+7=5 | | (y-15)-(1y-10)=19 | | 3(2x-5)-4(x-1)=(-3x-6)-3(x+3) | | 5*x+3=13 | | -9x-24=-11x+10 | | -6t=-39 | | log(x+15)-log(x)=0.65 |